Molecular simulations of venom peptide‐membrane interactions: Progress and challenges. Issue 3 (9th March 2018) - Deplazes, Evelyne
Abstract: Because of their wide range of biological activities venom peptides are a valuable source of lead molecules for the development of pharmaceuticals, pharmacological tools and insecticides. Many venom peptides work by modulating the activity of ion channels and receptors or by irreversibly damaging cell membranes. In many cases, the mechanism of action is intrinsically linked to the ability of the peptide to bind to or partition into membranes. Thus, understanding the biological activity of these venom peptides requires characterizing their membrane binding properties. This review presents an overview of the recent developments and challenges in using biomolecular simulations to study venom peptide‐membrane interactions. The review is focused on (i) gating modifier peptides that target voltage‐gated ion channels, (ii) venom peptides that inhibit mechanosensitive ion channels, and (iii) pore‐forming venom peptides. The methods and approaches used to study venom peptide‐membrane interactions are discussed with a particular focus on the challenges specific to these systems and the type of questions that can (and cannot) be addressed using state‐of‐the‐art simulation techniques. The review concludes with an outlook on future aims and directions in the field. Abstract :